2021
DOI: 10.33774/chemrxiv-2021-vsd4j-v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virtual computational chemistry teaching laboratories – hands-on at a distance

Abstract: The COVID-19 pandemic disrupted chemistry teaching practices globally as many courses were forced online necessitating adaptation to the digital platform. The biggest impact was to the practical component of the chemistry curriculum -the so-called wet lab. Naively, it would be thought that computer-based teaching labs would have little problem in making the move. However, this is not the case as there are many unrecognised differences between delivering computer-based teaching in-person and virtually: software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…In this work, we will show that free and open source software (FOSS) can be used in the context of the BYOD paradigm to achieve computational chemistry for the masses, all the while democratizing science by tearing down established power structures and barriers for research and education. (Inroads into BYOD in the context of virtual laboratories have also been recently discussed by Kobayashi et al 24 )…”
Section: Introductionmentioning
confidence: 87%
“…In this work, we will show that free and open source software (FOSS) can be used in the context of the BYOD paradigm to achieve computational chemistry for the masses, all the while democratizing science by tearing down established power structures and barriers for research and education. (Inroads into BYOD in the context of virtual laboratories have also been recently discussed by Kobayashi et al 24 )…”
Section: Introductionmentioning
confidence: 87%
“…However, the integration of computational chemistry in undergraduate teaching is hampered by a lack of user-friendly and easily accessible software/hardware environments and instructors with adequate training. 47,56 The eChem project is designed to break these barriers.…”
Section: Designing a Course Module Or Workhopmentioning
confidence: 99%
“…68,69 In addition, Kobayashi et al from the Australian National University demonstrated through a remote and hands-on computational chemistry course that virtual delivery of "dry" laboratories shows promise of effective engagement but is very technology-dependent. 33 Another facet of computer-based learning is data analysis laboratories, which give students the opportunity to gain hands-on experience with characterization, data processing, and interpretation techniques. Data analysis can easily be completed at home by providing students with raw data; although in some cases, it requires an online training component to make students more familiar with the analysis software (e.g., MestReNova, ChemDraw), data interpretation, and/or structure elucidation.…”
Section: Video-based Laboratoriesmentioning
confidence: 99%
“…Virtual Lab Strategies with Associated Main Concepts Covered, Assessment Methods Used, and the Level and Domain a,b 29,30,32,33,45,75,8898 …”
mentioning
confidence: 99%